Medullary thick ascending limb impairment in the GlatmTg(CAG‐A4GALT) Fabry model mice. Issue 8 (19th March 2018) - Maruyama, Hiroki; Taguchi, Atsumi; Nishikawa, Yuji; Guili, Chu; Mikame, Mariko; Nameta, Masaaki; Yamaguchi, Yutaka; Ueno, Mitsuhiro; Imai, Naofumi; Ito, Yumi; Nakagawa, Takahiko; Narita, Ichiei; et al.
Abstract : A main feature of Fabry disease is nephropathy, with polyuria an early manifestation; however, the mechanism that underlies polyuria and affected tubules is unknown. To increase globotriaosylceramide (Gb3) levels, we previously crossbred asymptomatic Glα tm mice with transgenic mice that expressed human Gb3 synthase (A4GALT) and generated the Gla tm Tg(CAG‐A4GALT ) symptomatic Fabry model mice. Additional analyses revealed that these mice exhibit polyuria and renal dysfunction without remarkable glomerular damage. In the present study, we investigated the mechanism of polyuria and renal dysfunction in these mice. Gb3 accumulation was mostly detected in the medulla; medullary thick ascending limbs (mTALs) were the most vacuolated tubules. mTAL cells contained lamellar bodies and had lost their characteristic structure (i.e ., extensive infolding and numerous elongated mitochondria). Decreased expression of the major molecules—Na + ‐K + ‐ATPase, uromodulin, and Na + ‐K + ‐2Cl − cotransporter—that are involved in Na+ reabsorption in mTALs and the associated loss of urine‐concentrating ability resulted in progressive water‐ and salt‐loss phenotypes. Gla tm Tg(CAG‐A4GALT ) mice exhibited fibrosis around mTALs and renal dysfunction. These and other features were consistent with pathologic findings in patients with Fabry disease. Results demonstrate that mTAL dysfunction causes polyuria and renal impairment and contributes to the pathophysiology of Fabry nephropathy.—Maruyama, H., Taguchi, A., Nishikawa, Y., Guili, C., Mikame, M., Nameta, M., Yamaguchi, Y., Ueno, M., Imai, N., Ito, Y., Nakagawa, T., Narita, I., Ishii, S. Medullary thick ascending limb impairment in the GlatmTg(CAG‐A4GALT ) Fabry model mice. FASEB J . 32, 4544–4559 (2018). www.fasebj.org